The Role of TPQ in Forming the Religious Character of Children in Society - Atiqah Zahrah; Juliani; Isfah Nurhadillah Rizki; Khairunnisa Harahap; Nadilla Yolanda (Journal of Contemporary Gender and Child Studies, 2025)
This research seeks to elucidate the execution of Al-Qur'an educational activities at TPQ Abu Keumala Al-Aziziyah situated in Paya Geli Village and its influence on the development of children's religious character. TPQ, as a non-formal Islamic educational institution, primarily aims to impart a foundational comprehension of Islam by instructing in Qur'anic reading, prayer memorization, and religious practice. This research employs a descriptive qualitative methodology, utilizing data collection methods such as observation and interviews. The findings of the study suggest that educational activities are executed in alignment with predetermined schedules and methodologies, including reading and writing techniques, direct practice, and traditional approaches. This TPQ significantly contributes to the formation of children's religious identity through the influence of educators, the support provided by family and community environments, the implementation of diverse methodologies, and the employment of existing facilities and infrastructure. Notwithstanding the challenges posed by insufficient teaching personnel and infrastructure, TPQ Abu Keumala Al-’Aziziyah is dedicated to cultivating a generation of Qur'anic students who embody high moral standards and robust Islamic principles.